Transformasi Pembelajaran Digital Pendidikan Islam melalui Model Adaptive Islamic Digital Learning (AIDL): A Systematic Literature Review - Nurhayati, Nurhayati; Zulmasri, Zulmasri; Arifnal, Wezi; Satrial, Ardi; Noza, Nofri (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to identify concepts and patterns of digital learning integration in Islamic education at the elementary and secondary school levels. The approach used is a systematic literature review. The procedures used include: (1) searching for sources using Harzing's or Perish, (2) filtering literature using PRISMA software, (3) mapping research findings with data tabulation, (4) narrating with the help of AI ChatGPT and DeepSeek, and (5) analyzing with constructive-humanistic learning theory and relevant research results. This study found a concept of digital learning in Islamic education called the adaptive Islamic digital learning (AIDL) model. This model offers a conceptual synthesis that integrates the theory of technological pedagogical content knowledge (TPACK) with a constructivist-humanistic approach and Islamic character values in Islamic Religious Education. Teachers must be present as facilitators in learning to ensure the realization of Islamic character values. The implications of this research can serve as a guide for teachers in the use of digital media in Islamic Religious Education learning in elementary and secondary schools.